2007
DOI: 10.3155/1047-3289.57.4.457
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Burnings of Wax Apple Stubble and Rice Straw on Polychlorinated Dibenzo-p-Dioxin and Dibenzofuran Concentrations in Air and Soil

Abstract: Measurements of the concentrations of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) were made in ambient air, ash, and soil impacted by the open burning of wax apple and rice straw residues. Measurements showed that the mean PCDD/F concentration (0.458 pg I-TEQ/Nm 3 ; international toxicity equivalence) in air at two wax apple orchards during open burning increased markedly, ϳ8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…OCDD, OCDF, 1,2,3,4,6,7,8-HpCDD and 1,2,3,4,6,7,8-HpCDF were the four predominant congeners. This is the same case in the ambient air before rice straw open burning in the study of Kao et al [4]. Nevertheless, the most dominant congeners were different.…”
Section: Pcdd/fs In the Ambient Air Without Biomass Open Burningmentioning
confidence: 59%
See 2 more Smart Citations
“…OCDD, OCDF, 1,2,3,4,6,7,8-HpCDD and 1,2,3,4,6,7,8-HpCDF were the four predominant congeners. This is the same case in the ambient air before rice straw open burning in the study of Kao et al [4]. Nevertheless, the most dominant congeners were different.…”
Section: Pcdd/fs In the Ambient Air Without Biomass Open Burningmentioning
confidence: 59%
“…Lin et al [13] reported that emissions from open burning of rice straw were 4200 and 158,800 tonnes/year for the KC area and Taiwan, respectively. Furthermore, Kao et al [4] measured the concentrations of PCDD/Fs in ambient air which were impacted by the open burning of rice straw residue. They reported that the mean PCDD/F concentration (0.409 pg I-TEQ/Nm 3 ) in ambient air at a rice straw field was 4.6 times higher than that (0.089 pg I-TEQ/Nm 3 ) before open burning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The open burning of biomass during agricultural debris and forest fires, wildfires, and land-clearing operations has been found to release significant amounts of polycyclic aromatic hydrocarbons and PCDD/Fs. 9 The PCDD/F concentration in the ambient atmosphere is also possibly influenced by these agricultural activities. Furthermore, some heavily emission sources are also located in southern Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the burned residue from wood sawdust and other biomass could induce DNA strand breaks through in vivo or in vitro exposure (Pandey et al 2005;Bornholdt et al 2007), but the mechanism was not clear. Biomass combustion may produce a complex mixture of compounds, such as aldehydes, PAHs, volatile organic compounds, chlorinated dioxins, respirable particulate matter, and reactive oxygen species (Smith et al 1994;Nolte et al 2001;Long et al 2004;Kao et al 2007). Some of these compounds were known or suspected as genotoxic in exposure to animals and human (Tokiwa et al 1985;Yin et al 1998).…”
Section: Genotoxicity Of Ashmentioning
confidence: 98%